Manajemen Sekuriti pada Perusahaan Samsung Electronics Indonesia - Edy Susanto; Husni Ramhadan; Ivan Ardiansyah; Rizky Maulan (Jurnal Ilmiah Wahana Pendidikan, 2023)
During this time, the basic need for security has been established since the founding of the company. However, security measures are carried out only as they are, not consciously through more mature planning. In its activities, security management ensures that information resources remain secure and alert to their integrity, confidentiality, and availability so that they can minimize losses when unwanted things happen. Security management is to ensure that assets (buildings, machines), human resources (employees, visitors), and information systems (data, application programs) remain secure. The task and function of security management are to organize the safety and order in the environment or work area to prevent any disturbance of order and order or other violations of the rules of the company. Securities management is a part of overall management that covers the organizational structure, planning, responsibilities, implementation, procedures, processes, and resources necessary for the development, application, achievement, assessment, and maintenance of security policies in order to control the risks associated with business activities. Security management is based on the processing of data that is then analyzed about an event that has already occurred or may occur in a locality or environment. Security management is not only expected to keep information resources secure but also to keep the company functioning after a disaster or collapse of the security system.